2021
DOI: 10.1038/s41598-021-97467-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic transcriptome analysis reveals altered lipid metabolism and consequent health indices in chicken supplemented with dietary Bifidobacterium bifidum and mannan-oligosaccharides

Abstract: This study investigated the role of dietary prebiotic mannan-oligosaccharides (MOS), and probiotic Bifidobacterium bifidum (BFD) in lipid metabolism, deposition, and consequent health indices in broiler chicken. The supplementation of 0.2% MOS along with either 106 or 107 CFU BFD/g feed resulted in downregulation of Acetyl-CoA carboxylase, fatty acid synthase, sterolregulatory element binding protein-1, and apolipoprotein B100; and up-regulation of peroxisome proliferator activated receptor-α AMP-activated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Notably, the relative abundance of some beneficial bacteria such as Bifidobacterium, Ruminococcus and Enterococcus were also increased in the OEO group. Some species from Enterococcus such as E. faecium and E. faecalis and Bifidobacterium are known as natural probiotics on account of their multiple health-promoting effects in animal production (57)(58)(59)(60). It has been reported that omnivorous beetles enriched with Enterococcus bacterium have the ability to more efficiently digest a greater volume of food (61).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the relative abundance of some beneficial bacteria such as Bifidobacterium, Ruminococcus and Enterococcus were also increased in the OEO group. Some species from Enterococcus such as E. faecium and E. faecalis and Bifidobacterium are known as natural probiotics on account of their multiple health-promoting effects in animal production (57)(58)(59)(60). It has been reported that omnivorous beetles enriched with Enterococcus bacterium have the ability to more efficiently digest a greater volume of food (61).…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium genus has been discovered recently, but recent data suggest that it is commonly found within the cecum of chickens and has been found to show performance-and growthpromoting activity associated with broiler chickens [46,47]. Within the Actinobacteria phylum, there are mostly gram-positive soil bacteria such as Bifidobacterium, a known probiotic bacterium that has been studied and implemented in chicken models, which exhibited an improvement in health parameters as well as demonstrated the potential to reduce the colonization of commonly known gram-negative foodborne pathogenic bacteria [48,49]. The Proteobacteria phylum is most associated with harboring a vast array of common gram-negative pathogenic bacteria, including those belonging to the genus of Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] In vitro fermentation demonstrated that CMOS promoted the growth of various Bifidobacterium and Lactobacillus strains. [ 25 ] These study showed that MOS promoted the proliferation of beneficial bacteria, leading to a more balanced and diverse gut microbiota. By reducing the relative abundance of pro‐inflammatory microbiota, MOS may help to alleviate inflammation‐related conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] MOS and Bifidobacterium bifidum can regulate lipid and cholesterol metabolism to decrease the atherogenic coefficient of broiler chickens. [25] Interestingly, addition of MOS derived from the yeast Saccharomyces cerevisiae to the diet effectively decreased the onset of AS development via modulating gut microbiota, increasing fecal excretion of bile acid, and decreasing cholesterol concentration in female E3L.CETP mice, while the specific markers of systemic inflammation were not affected. [26] Manno-oligosaccharides from cassia seed gum (CMOS) not only regulate the gut microbiota in vivo and in vitro, but also ameliorate inflammation and maintain intestinal barrier integrity in diabetic rats.…”
Section: Wwwadvancedsciencenewscom Wwwmnf-journalcommentioning
confidence: 99%
See 1 more Smart Citation